ANK2 functionally interacts with KCNH2 aggravating long QT syndrome in a double mutation carrier - Geßner, Guido; Runge, Sarah; Koenen, Michael; Heinemann, Stefan H.; Koenen, Mascha; Haas, Jan; Meder, Benjamin; Thomas, Dierk; Katus, Hugo; Schweizer, Patrick Alexander (Biochemical and biophysical research communications, 2019)
Pathogenic long QT mutations often comprise high phenotypic variability and particularly variants in ANK2 (long QT syndrome 4) frequently lack QT prolongation. We sought to elucidate the genetic and functional background underlying the clinical diversity in a 3-generation family with different cardiac arrhythmias. Next-generation sequencing-based screening of patients with QT prolongation identified the index patient of the family carrying an ANK2-E1813K variant and a previously uncharacterized KCNH2-H562R mutation in a double heterozygous conformation. The patient presented with a severe clinical phenotype including a markedly prolonged QTc interval (544ms), recurrent syncope due to Torsade de Pointes tachycardias, survived cardiopulmonary resuscitation, progressive cardiac conduction defect, and atrial fibrillation. Evaluation of other family members identified a sister and a niece solely carrying the ANK2-E1813K variant, who showed age-related conduction disease. An asymptomatic second sister solely carried the KCNH2-H562R mutation. Voltage-clamp recordings in Xenopus oocytes revealed that KCNH2-H562R subunits were non-functional but did not exert dominant-negative effects on wild-type subunits. Expression of KCNH2-H562R in HEK293cells showed a trafficking deficiency. Co-expression of the C-terminal regulatory domain of ANK2 in Xenopus oocytes revealed that ANK2-E1813K diminished currents mediated by the combination of wild-type and H562R KCNH2 subunits. Our data suggest that ANK2 functionally interacts with KCNH2 leading to a stronger current suppression and marked aggravation of long QT syndrome in the patient carrying variants in both proteins.
Gesehen am 24.02.2020